Powder Technology - Adriano Cavalheiro, Alberto (IntechOpen, 2018)
Powder Technology comprehends several particulate solid systems, which must be controlled, from the nucleation stages to the final application of derivative materials. Powder characteristics depend on the synthesis method, which can be a simple solid-state reaction followed by attrition milling, mechanosynthesis, or chemical methods, such as the sol-gel method. Powder technology is an important interdisciplinary area, which can provide solutions to several application fields. The book Powder Technology contains several peer-reviewed chapters organized in two sections. Section 1 is focused on metal and composites powders and Section 2 contains chapters on non-metallic powders. I sincerely hope that the contents of this book will help in the dissemination of knowledge to researchers and students working with powder technology.